2019
DOI: 10.21037/atm.2019.09.138
|View full text |Cite
|
Sign up to set email alerts
|

Impact of negative lymph nodes on colon cancer survival and exploring relevant transcriptomics differences through real-world data analyses

Abstract: Background: The prognostic role and underlying heterogeneity of negative lymph nodes (NLNs) on colon cancer is not well understood. The purpose of this study was to construct NLN-based prognostic models and reveal relevant mechanisms affecting NLNs by analyzing omic data.Methods: This inception cohort study included 314,398 colon cancer patients from the US Surveillance, Epidemiology, and End Results (SEER) database. Receiver operating characteristic (ROC) curve was used to determine the cut-off of NLNs. Nomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The different biological processes between the high and low NLN group through transcriptomic analysis (14).…”
Section: Discussionmentioning
confidence: 99%
“…The different biological processes between the high and low NLN group through transcriptomic analysis (14).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with nonmetastatic colon cancer, the higher the number of harvested lymph nodes, the better the oncological prognosis. The ratio of the involved lymph nodes to the harvested lymph nodes was identified as a strong prognostic indicator in stage III patients [ 64 , 65 ]. Although it is true that the removal of more lymph nodes by extended radical lymph node dissection is reflecting favorable prognosis, it requires considerable caution in interpreting this correlation as a cause-and-effect relationship.…”
Section: Oncological Necessity Of Complete Mesocolic Excision With Central Vascular Ligationmentioning
confidence: 99%
“…The number of NLNs was obtained by subtracting the number of PLNs from the total number of RLNs. The NLN intervals were as follows: NLN1 (≤7), NLN2 (8)(9)(10)(11)(12)(13), and NLN3 (≥14).…”
Section: Lymph Node Classificationsmentioning
confidence: 99%
“…Several studies have also demonstrated that the number of NLNs is positively correlated with the OS of EC patients 11 . The higher the number of NLNs a patient has, the better the prognosis 12, 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation